FINANCIAL SATISFACTION DETERMINANTS FROM HOME INDUSTRY IN SURABAYA - Fernando, Jovian; Handoko, Jesica (Jurnal Akuntansi Bisnis, 2024)
Background: Financial satisfaction is one of the goals that every entrepreneur wants to achieve, which requires sacrifice of resources such as capital, time, energy, and other things to obtain it. Financial satisfaction is also the goal of a home business which is currently growing rapidly in Indonesia..Purpose: The purpose of this research is to examine the effect of income, financial literacy, financial attitudes, and financial distress on the financial satisfaction of home-based business owners in the city of Surabaya.Method: The convenience sampling method will be used to get 100 home-based business respondents in the city of Surabaya, both businesses that were established before or during the COVID-19 pandemic. Data collection was carried out by distributing questionnaires and the data was processed using SPSS software.Results: The results of this study indicate that only income and financial attitudes have a positive and significant effect on financial satisfaction, while financial literacy and financial distress do not affect financial satisfaction.Research Novelty: This research is a small amount of research that focuses on the achievements of home-based businesses that are thought to have the ability to survive during a pandemic. The findings prove that financial difficulties are not able to reduce their financial satisfaction.